2008
DOI: 10.1002/casp.936
|View full text |Cite
|
Sign up to set email alerts
|

‘Who would take whose name?’ Accounts of naming practices in same‐sex relationships

Abstract: The practice of a woman assuming her husband's last name upon marriage is a deeply embedded norm in some countries. Whether or not individual heterosexual couples reproduce or resist this practice, it provides a context for making decisions about marital names. No conventions, other than heteronormative ones, govern naming practices in same-sex relationships and families, but very little is known about name changing in these contexts. This paper reports an exploratory qualitative study of the ways in which 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…Consistent with previous findings, we found that heterosexual couples commonly followed patronymic conventions, such that both parents and their children were likely to have the same last names (Gooding & Kreider, 2010). Also consistent with previous results, heterosexual parents generally explained these choices by referring to tradition (Clarke et al, 2008). Lesbian and gay couples, in contrast, took very different approaches to naming themselves and their children.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous findings, we found that heterosexual couples commonly followed patronymic conventions, such that both parents and their children were likely to have the same last names (Gooding & Kreider, 2010). Also consistent with previous results, heterosexual parents generally explained these choices by referring to tradition (Clarke et al, 2008). Lesbian and gay couples, in contrast, took very different approaches to naming themselves and their children.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, although other options were sometimes considered, the most common choice among same-sex couples was for both members of the couple to retain the last names they had been given at birth. As might be expected, various justifications were offered by those who did or did not change their names (Clarke et al, 2008;Suter & Oswald, 2003). Interestingly, the likelihood of lesbians' having changed last names was not associated with whether or not they had undertaken a commitment ceremony.…”
Section: Last Names Of Adults In Same-sex and Other-sex Relationshipsmentioning
confidence: 84%
See 2 more Smart Citations
“…Furthermore, most partners reported a desire to retain as separate, any assets or savings that they had brought into the relationship in addition to a portion of their income. This co-independence or inter-dependence was upheld as an ideal even for those considering a Civil Partnership (with its potential assistance with dividing relationship property in the event of dissolution) (see Clarke et al, 2006). That so many couples in this study privileged some degree of financial autonomy raises serious questions about some of the assumptions and responsibilities in the legislation such as: "registered partners would be expected to share their financial resources and should therefore be treated as a single family [financial?]…”
Section: Discussionmentioning
confidence: 99%